Measles epidemiological surveillance system before and during the COVID-19 pandemic in Pernambuco, Brazil, 2018-2022: a descriptive evaluation - Cinthia Regina Albuquerque de Souza; Lygia Carmen de Moraes Vanderlei; Paulo Germano de Frias (Epidemiologia e Serviços de Saúde, 2023)
Abstract Objective: To evaluate the measles epidemiological surveillance system, before and during the COVID-19 pandemic in Pernambuco, Brazil. Methods: This was a descriptive evaluation of the quality (duplicity; completeness; consistency), timeliness and usefulness attributed, classified as excellent ≥ 90.0%, regular ≥ 70.0% and < 90.0%, and poor (< 70.0%). Data from the Notifiable Health Conditions Information System and Laboratory Environment Management System were used, before (03/11/2018-03/10/2020) and during (03/11/2020-03/10/2022) the pandemic. Results: 1,548 suspected measles cases were registered (1,469 before and 79 during the pandemic). In the two periods studied, there were 11 and 1 duplicate records, average completeness in filling out the variables was 99.2% and 95.7%, while average consistency was 96.7% and 97.5%, respectively. Timeliness (receipt of samples, 16.2% and 33.0%. Release of results, 1.3% and 1.3%) and usefulness (43.5% and 24.4%) were poor. Conclusion: Quality was classified as excellent in the periods studied, timeliness and usefulness were classified as poor, signaling non-compliance with the purpose of the system.